Partisipasi Masyarakat Dalam Penyusunan APBDes di Desa Pait Kecamatan Kasembon Kabupaten Malang Tahun Anggaran 2019 - Krishno Hadi; Iradhad Taqwa Sihidi; Mariano Werefrindus (Sawala : Jurnal Administrasi Negara, 2022)
This study aims to determine community participation in the preparation of APBDES in Pait Village, Kasembon District, Malang Regency for Fiscal Year 2019. The method used is descriptive with a qualitative approach and analyses data sourced from in-depth interviews, direct observation, literature review, and documentation. The results obtained indicate that community participation in the preparation of the APBDes village income budget is participation through thinking by providing ideas or opinions in the preparation of the Pait Village APBDes what is desired by the community and then considered by the village government in budgeting. Supporting factors are 1) Education level, supporting human resources are expected to be able to provide more substantial proposals, ideas, or opinions about what needs are necessary and urgent 2) The type of work determines what aspirations and participation can be provided through village activities. While the inhibiting factor is that not all proposals submitted by the community through the hamlet or village deliberation forums are accommodated into programs. Overall, it shows that Pait Village residents' level of participation and enthusiasm is very high in every process of preparing the Pait Village APBDes.